Edge of the city [videorecording (DVD)] - Ritt, Martin, 1914-1990; Cassavetes, John, 1929-1989; Poitier, Sidney; Warden, Jack; Maguire, Kathleen, 1925-1989; Dee, Ruby (Distributed by Warner Home Video, 2009)
If you need a job Charlie Malik can find a spot for you in the dockside railyards. All he needs in return is that you show up on time, work hard, and kick back part of your pay. Two New York City longshoremen, Axel Nordmann, an Army deserter, and Tommy Tyler, an easy-going freight car loader, join forces against a corrupt New York waterfront union official. The two share a bond that cuts across society's black/white divide.